Shocks and health care in Latin America and the Caribbean - Marcia C. Castro; Jamie Ponmattam; Emily A. FitzGerald (Frontiers in Public Health)
BackgroundThe Latin American and the Caribbean (LAC) is one of the most disaster-prone regions worldwide, and the frequency and intensity of disasters is expected to increase. We propose typologies of shocks considering healthcare resilience to examine how the risk of shocks varies across LAC and how previous shocks and their impacts in LAC fit into these categories.MethodsWe classify shocks into natural, anthropogenic and climate-related, and build on the literature to develop a 2×2 classification considering health care resilience and trust in government. Using the INFORM risk we categorize countries into risk groups considering indicators of governance and access to healthcare as proxies for trust in government and health care resilience, respectively. We discuss the 2×2 classification considering examples of health impacts of shocks, highlighting strengths and weaknesses of national responses, and use excess death ratios during the COVID-19 pandemic to demonstrate how health impacts correspond to the 2×2 typology.ResultsBased on the available literature, the proposed 2×2 classification reflects the recent consequences of shocks in LAC countries. Overall, areas where healthcare access and trust in government were weak had the most devastating impacts. However, strong access to healthcare is not a sufficient condition determining the impact of a shock, as evidenced during the COVID-19 pandemic. For the most part, countries lack a detailed shock management plan.DiscussionCountries in the LAC region have historically been unprepared to manage shocks. In the absence of a comprehensive and multisectoral shock management plan, countries will continue to act in a reactive way, after a shock, as most of the examples discussed in our analysis illustrate. A shock management plan is an important step to build resilient health systems.